Empowering Kennel Associates at Veterinary Practices: Win-Win Strategies for Management and Employees - Jennifer E. Darby; Allen F. Wysocki (EDIS)
HR027, a 6-page fact sheet by Jennifer E. Darby and Allen F. Wysocki, outlines what it takes to create a positive work environment through effective communication, encouragement, rewards, training, and goal setting. Includes references. Published by the UF Department of Food and Resource Economics, April 2008.